2022
DOI: 10.1002/nop2.1249
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of being a second victim among Spanish midwives and obstetricians

Abstract: Aim The aim of this study was to determine the prevalence of feelings of being a second victim among midwives and obstetricians in Spain and to explore possible differences between the two professions. Design Cross‐sectional descriptive‐analytical observational study. Methods An online survey collecting several variables was administered throughout the Spanish territory. Spanish version of the Second Victim Experience and Support Tool (SVEST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…They indicated that they feel like they have let the patient down, impacting how they view themselves as health professionals. They doubt their skills and knowledge, negatively affecting their mental well-being (45). A study conducted by Kinman et al (53) concurred with the ndings of the previous author and added that poor mental health of staff has a detrimental effect on the quality of care.…”
Section: Sub-theme 41: Effective Communication and Collaborative Mana...mentioning
confidence: 79%
See 1 more Smart Citation
“…They indicated that they feel like they have let the patient down, impacting how they view themselves as health professionals. They doubt their skills and knowledge, negatively affecting their mental well-being (45). A study conducted by Kinman et al (53) concurred with the ndings of the previous author and added that poor mental health of staff has a detrimental effect on the quality of care.…”
Section: Sub-theme 41: Effective Communication and Collaborative Mana...mentioning
confidence: 79%
“…Lack of support of midwives after an adverse event by managers has a negative psychological impact on the midwives, contributing to the lack of desire to return to work (44). The above ndings were supported by Christoffersen et al (45), who found that midwives experience a lack of support from their supervisors during adverse events, in uencing the desire to leave employment without the nurse manager's awareness.…”
Section: Sub-theme 31: Visibility and Support During Patient Safety I...mentioning
confidence: 88%
“…This quantitative research found that the psychological, physical and practice distress of nurses as second victims after patient safety events was higher than in a previous survey of psychiatric nurses in China, 20 and the psychological distress was higher than that of Singaporean nurses 8 and Spanish midwives and obstetricians. 21 Yan et al found that nurses had higher levels of second-victim experience and support than other health professionals did. 22 This finding proves that the psychological, physical and practice distress of nurses in China are higher than those of other health care providers, which is consistent with the results of foreign studies.…”
Section: Discussionmentioning
confidence: 99%